STUDI KUALITATIF: PERAN HANDOVER DALAM MENINGKATKAN KESELAMATAN PASIEN DI RUMAH SAKIT - Rieibowo, Cecep; Harahap, Zainuddin; ., Soep (Universitas Pekalongan, 2016)
Background.The primary cause of adverse event and the incidence of injury almost (near miss) in the hospital is inaccurate information. To prevent it is necessary to accurate information about the state of the patient at every shift change by nurses (handover). The aimed of this study was to determine the relationship of the handoverimplementation and patient safety. Method. This study used qualitative studies. The participants in this study amounted to 7 nurses in Wards of Pirngadi Hospital Medan.Collecting data used in-depth interviews. Data analysis used interactive of analysis model. The results showed that majority of nurses not yet implemented handover very well although patient safety become a priority in nursing care. The conclusion of this study is handover can improve patient safety in hospitals.